IL‐9 promotes the survival and function of human melanoma‐infiltrating CD4+CD8+ double‐positive T cells. Issue 7 (6th May 2016) - Parrot, Tiphaine; Allard, Mathilde; Oger, Romain; Benlalam, Houssem; Raingeard de la Blétière, Diane; Coutolleau, Anne; Preisser, Laurence; Desfrançois, Juliette; Khammari, Amir; Dréno, Brigitte; Labarrière, Nathalie; Delneste, Yves; et al.
Abstract : Intra‐melanoma CD4 + CD8 + double positive T cells overexpress the IL‐9 receptor compared to their CD8 + T‐cell counterparts. IL‐9 would enhance their antitumor function while participating in their retention in the tumor microenvironment. Abstract : We previously demonstrated an accumulation of tumor‐reactive CD4 + CD8 + double positive (DP) T cells within melanoma‐infiltrating lymphocytes, supporting their role in the regulation of anti‐tumor immune responses. Similarly to their CD8 + counterparts, intra‐tumor DP T cells are MHC class‐I restricted but differed by a limited lytic activity against autologous melanoma cells. Based on these observations and to further characterize DP T cells, both populations were compared at the transcriptional level. Our results revealed the overexpression of the IL‐9 receptor (IL‐9R) by DP T cells and prompted us to investigate the impact of IL‐9 on their biology. We show that IL‐9 favors DP T‐cell survival by protecting them from apoptosis and by promoting their proliferation. In addition, IL‐9 enhances their ability to produce cytokines and increased their levels of granzyme B/perforin as well as degranulation capacity, leading to a strengthened cytotoxic activity against melanoma cells. Taken together, the IL‐9R high DP T‐cell population could be a new preferential target for IL‐9, which could take part in their retention within the melanoma infiltrate while also favoring their anti‐tumor activity. More generally, our results extend the pleiotropic effects of IL‐9 to IL‐9R‐expressing intra‐tumor T cells, which could further potentiate anti‐tumor immune responses.